2017
DOI: 10.1097/md.0000000000008301
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hydrophobic and hydrophilic intraocular lens in preventing posterior capsule opacification after cataract surgery

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 25 publications
5
54
2
4
Order By: Relevance
“…As reported, capsule space was positively related to axial length, the longer eyes had a larger capsule [6] and the implanted IOL was thinner, which tended to have less convexity of the IOL back surface. In addition, IOL apposition to capsule was negatively correlated with axial length [15]. These factors resulted in a larger IOL-PC space and higher PCO occurrence rate which could be supported by our results as well.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As reported, capsule space was positively related to axial length, the longer eyes had a larger capsule [6] and the implanted IOL was thinner, which tended to have less convexity of the IOL back surface. In addition, IOL apposition to capsule was negatively correlated with axial length [15]. These factors resulted in a larger IOL-PC space and higher PCO occurrence rate which could be supported by our results as well.…”
Section: Discussionsupporting
confidence: 88%
“…As it was reported that the rapid proliferation speed of LECs for patients younger than 40 years was only 5.8 ± 0.6 days, for those who were older than 60 years was 7.2 ± 0.7 days. Hence, theoretically, LECs could migrate to and proliferate on the posterior capsule before capsular bend formation (1 month after surgery [11]) and IOL apposition to a capsule (within 2 weeks for normal eyes [13,14] and en-longed for high myopia eyes [15]). In addition, Elgohary et al [19] reported closer apposition between IOL optic and mid-peripheral posterior capsules when comparing hydrophobic acrylic IOLs and PH silicone IOLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which the opacification was resolved are unknown. However, this fact should be considered when implanting hydrophobic lenses along with another advantage, which is the lower incidence of posterior capsule opacification compared to hydrophilic lenses …”
Section: Discussionmentioning
confidence: 99%
“…Phacoemulsification is a satisfactory method for the treatment of cataract, but there are also many postoperative complications [5] [6] [7]. Posterior capsular opacification (PCO) is the most common complication after a few years of surgery [8]. Therefore, the prevention and treatment of cataract has become particularly important.…”
Section: Introductionmentioning
confidence: 99%